Mogens Pedersøns madrigaler og madrigaletter: En dansk komponists forhold til den italienske vokalmusik på overgangen mellem det 16. og 17. århundrede - Messina, Kitti (Danish Yearbook of Musicology, 2001)
Mogens Pedersøn, a composer of remarkable talent at the Court of King Christian IV, visited Italy twice, specifically Venice, to learn the traditional compositional technique of polyphonic madrigals from Giovanni Gabrieli. He published one book containing 21 five-voice madrigals, and presumably another book of which only ten five-voice madrigals have survived in the English manuscript, London, British Library Egerton 3665 (the so-called “Tregian manuscript”). He also composed two small three-voice madrigaletti. The comparison of some of his secular vocal compositions with music settings of the same poetical texts by other Italian composers (particularly Amante Franzoni and Francesco Di Gregorii) shows that Pedersøn knew and chose some ‘lighter’ genres (three-voice strophic songs, in some cases with instrumental accompaniment) as models for his five-voice and three-voice madrigals.